Effect of natural zeolite on digestibility of nutrients in goats fed high concentrate diets - Hayatunnisak Talibin. (2012)
In this study, effect of different levels of zeolites on digestibility of nutrient in goats fed high concentrate diets based on PKC was investigated. In a cross-over design experiment (4 treatments over 3 periods) eight local female Kacang crosses, with an average live weight 28±2 kg were randomly selected and two goats were allotted to each of the four dietary treatment. Each period consisted of 14 days adjustment period followed by 7 days collection of faecal and urine output. The goats were fed individually at the rate 3% body weight. The four dietary treatments were Control (20% rice straw and 80% concentrates) which was the basal diet, (Diet 1) or basal diet supplemented with 0.5% (diet 2), 1.0% (diet 3) and 1.5% (diet 4) zeolites. The rations were fed to goats as total mixed feed; offered feed, residue, feaces and urine were recorded daily in early morning during seven days in each period. Feed intake per day was higher for goats receiving zeolites (P<0.05) but feed intake per kg BW was not significantly affected (P>0.05) by treatment but tended to be higher with added zeolites however digestibility of OM was not significantly affected (P>0.05). Digestibility of OM, CP, ADF and NDF was higher with added zeolite (P<0.05) by inclusion of 1.5% zeolite is the highest. As well as retention of mineral Ca and N was higher (P<0.05) with added zeolites. Conversely the retention of mineral P and Cu was not significantly affected (P>0.05).